The Shirley brothers and their role in the Safavid state 1528-1598 AD - Dr. Oday Sami Faris (Journal of College of Education, 2026)
At the beginning of the seventeenth century، the English brothers Anthony and Robert Sherley emerged as pivotal players in the political and military interactions between the Safavid Empire and Europe. They arrived in Iran in 1598 AD، during the reign of Shah Abbas I، bringing European military expertise and organizational techniques that contributed to the restructuring of the Safavid army and the development of its combat capabilities، particularly in the use of firearms and artillery. Anthony Sherley played a military advisory role، focusing on modernizing military formations and establishing training foundations in accordance with European standards. He also played a diplomatic role، establishing political، military، and commercial relations between Iran and European countries to confront the Ottoman Empire. Meanwhile، Robert Sherley undertook high-level military and diplomatic duties، leading Iranian missions to European kingdoms such as Spain، Italy، Poland، and Russia، with the aim of forming alliances aimed at limiting Ottoman influence and enhancing trade and political exchanges. These efforts contributed to consolidating the Safavid state’s position as a regional power with an international dimension and to expanding its contacts with European powers. The Shirley brothers thus formed a strategic bridge between East and West، and their presence had a profound impact on the development of the Safavid military and diplomatic structure